Use of Botanicals for Management of Weevil (Sitophilus zeamais motschulky) in Maize Storage (Journal of Agriculture and Environment, 2022)
A laboratory study was conducted with the aim of evaluating efficacy of different botanical insecticides against weevil in storage with four replication in completely randomized design. Seven plant materials; Acorus calamus Linn., Piper nigrum Linn., Zanthoxylum armatum DC., Azedarachta indica A. Juss., Melia azedarach Linn., Justicia adhatoda Linn., and Artemisia vulgaris Linn. were compared along with control. Maize samples were infested with S. zeamais at the rate of 4 pair adults/50 g. At 120 days of treatment, the highest and lowest number of weevil progeny (19.75 and 0.70), and grain damage % (19.50% and 0.21%) was recorded in control and A. calamus. Similarly, weight loss% was the highest on control (7.03%) and lowest on A. calamus (1.80%), followed by A. indica (2.79%) and P. nigrum (3.13%), respectively.100% weevil mortality was observed in A. calamus and P. nigrum treated grains within 14 and 21 days. A. calamus was found more effective for weevil management in storage.